Eimeriosis in Poultry: Biology, Spread and Control Measures in the Caspian Sea Region of the Russian Federation - A. B. Dagayeva; R. М. Bakrieva; B. M. Makhieva (Российский паразитологический журнал, 2020)
The purpose of the research is determining treatment and protective efficacy of modern drugs at eimeriosis in poultry under production conditions.Materials and methods. The work was carried out in a laboratory for invasion diseases of farm animals and poultry of the Caspian Zonal Scientific Research Veterinary Institute, and in the Republic poultry farms. Using Fulleborn’s method, there were 500 excrement samples from chicken aged 1–3 months and laying hens tested, autopsy of 87 birds carried out, and morphological traits of their structure studied, based on which Eimeria tenella and E. necatrix were differentiated. The treatment and protective efficacy of Eimeterm 2.5% was tested in combination with Enrofloxacin in a dose of 3.0 ml per 1 liter of drinking water within 5–6 days. The drugs were given to floor housed broiler chickens with water to drink, namely, Eimeterm was given for two consecutive days in a dose of 7.0 mg/kg of bird weight (28 ml per 100 kg of bird weight), which is equal to 1 ml of the drug per 1 liter of drinking water within 48 hours, or 3 ml of the drug per 1 liter of drinking water which was given to a bird to drink for 8 hours in a day two consecutive days, and Enrofloxacin in a dose of 3.0 ml per 1 liter of drinking water within 5–6 days as compared to basic drug Amprolium. In another poultry house, test broiler chickens were administered 7.5 g of Amprolium 20% in powder form mixed with 1 kg of feed within 7–8 days. The therapeutic efficacy was evaluated by the results of coproscopic examinations and scrapes from different floor sections. A sample autopsy of chickens was carried out to find any morphological change in the digestive tract and Coccidia; intestinal mucosa swabs were tested using the Darling’s method, which was standardized by N. P. Orlov. The results obtained were processed statistically.Results and discussion. The results of broiler chickens’ cecum examinations revealed a high rate of Eimeria infection. Thus, 20–30 oocysts were found in 55 samples in a single microscope field representing 63.2%. The oocysts referred to four species: Е. tenella, E. maxima and Е. mitis in the cecum and small bowel, and E. accervulina in the duodenum. 100% efficacy of Eimeterm 2.5% and Enrofloxacin when combined with water was confirmed. The mortality rate reduced from 137 to 11 animals per day. The survivability of broiler chickens in the test group in the growing period was 94.3%. The autopsy of broiler chickens showed no Eimeriosis-specific changes in the visceras. The tests of 200 cecum swabs and scatoscopy of 20 excrement samples found no Eimeria oocysts.